2018
DOI: 10.1038/s41598-018-28977-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil evaporation and organic matter turnover in the Sub-Taiga and Forest-Steppe of southwest Siberia

Abstract: Southwest Siberia encompasses the forest-steppe and sub-taiga climatic zones and has historically been utilized for agriculture. Coinciding with predicted changes in climate for the region is the pressure of agricultural development; however, a characterization of the soil water and carbon dynamics is lacking. We assessed current soil water properties and soil organic carbon turnover in forests and grasslands for two sites that span the forest steppe and sub-taiga bioclimatic zones. Soil evaporation was 0.62 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…This phenomenon, also known from previous laboratory scale studies, is indicated by replacing δ 18 O‐N 2 O by Δδ 18 O(H 2 O/N 2 O) as the difference of δ 18 O values between the soil water (δ 18 O‐H 2 O) and the product (δ 18 O‐N 2 O) (Lewicka‐Szczebak et al, 2014; Lewicka‐Szczebak et al, 2016; Well et al, 2008; Zhu et al, 2013). The enrichment of Δδ 18 O(H 2 O/N 2 O) during drying or dry periods (Figures 3 and S9) supports the notion that besides N 2 O reduction, evaporative 18 O‐enrichment of δ 18 O‐H 2 O soil water affects Δδ 18 O(H 2 O/N 2 O) values, which is also in accordance with previous observations (Benettin et al, 2018; Kayler et al, 2018; Sprenger et al, 2017). This indicates that, in summary, the variability of Δδ 18 O(H 2 O/N 2 O) can be explained by the effects of (i) mixing of precipitation water and soil water with subsequent oxygen exchange between soil water and NO 3 − , (ii) evaporative 18 O‐enrichment of soil water and propagation of 18 O enriched water to NO 3 − , and (iii) N 2 O reduction on Δδ 18 O(H 2 O/N 2 O).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This phenomenon, also known from previous laboratory scale studies, is indicated by replacing δ 18 O‐N 2 O by Δδ 18 O(H 2 O/N 2 O) as the difference of δ 18 O values between the soil water (δ 18 O‐H 2 O) and the product (δ 18 O‐N 2 O) (Lewicka‐Szczebak et al, 2014; Lewicka‐Szczebak et al, 2016; Well et al, 2008; Zhu et al, 2013). The enrichment of Δδ 18 O(H 2 O/N 2 O) during drying or dry periods (Figures 3 and S9) supports the notion that besides N 2 O reduction, evaporative 18 O‐enrichment of δ 18 O‐H 2 O soil water affects Δδ 18 O(H 2 O/N 2 O) values, which is also in accordance with previous observations (Benettin et al, 2018; Kayler et al, 2018; Sprenger et al, 2017). This indicates that, in summary, the variability of Δδ 18 O(H 2 O/N 2 O) can be explained by the effects of (i) mixing of precipitation water and soil water with subsequent oxygen exchange between soil water and NO 3 − , (ii) evaporative 18 O‐enrichment of soil water and propagation of 18 O enriched water to NO 3 − , and (iii) N 2 O reduction on Δδ 18 O(H 2 O/N 2 O).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the two process domains N 2 O D and N 2 O N together with N 2 O reduction to N 2 are assumed to be the only parameters influencing the final observed SP and δ 18 O(H 2 O/N 2 O) values. In contrast, as outlined in section 4.2, evaporative 18 O enrichment (Benettin et al, 2018; Kayler et al, 2018; Sprenger et al, 2017) and the extent of O exchange between soil water and precipitation (Lewicka‐Szczebak et al, 2014; Lewicka‐Szczebak et al, 2016; Well et al, 2008; Zhu et al, 2013) may have systematically influenced the observed δ 18 O(H 2 O/N 2 O) values in this study, because we observed a wide range of WFPS values during the measurement campaign. This is based on the notion that nitrification played a minor role during the measurement campaign and that increases in WFPS should be accompanied with enrichment in δ 18 O(H 2 O/N 2 O) due to an increasing share of N 2 O reduction to N 2 , which however was in contrast to observations.…”
Section: Discussionmentioning
confidence: 99%
“…LTA molecular sieve membrane is widely used in industry to selectively remove water from organic matter by pervaporation [35]. For LTA molecular sieves, the maximum dynamic diameter of molecules capable of diffusing in their channels is 0.42 nm.…”
Section: Preparation Of Lta Powdermentioning
confidence: 99%
“…In addition to the effects of climate and soil, transpiration and variability in the shade provided by vegetation can strongly influence soil evaporation loss by controlling soil water status and the microclimate in forest ecosystems, while knowledge of the effects of vegetation on soil evaporation and, consequently, on lc-excess is limited [21][22][23]. Soil evaporation loss is mainly controlled by atmospheric demand and soil water supply, which influences lc-excess by regulating soil evaporation fractionation factors and soil residual water storage [3].…”
Section: Introductionmentioning
confidence: 99%
“…Soil water supply for evaporation can be influenced by soil water content, which is affected by precipitation infiltration, transpiration and percolation [25]. Vegetation coverage alters atmospheric demand by intercepting solar radiation and affecting ground relative humidity [26] and changes the soil water supply by intercepting precipitation and absorbing soil water [22]. During the dry season, a positive However, precipitation inputs by infiltration and percolation of water from the upper soil layers may hinder the capacity of lc-excess to indicate the soil evaporation loss (Figure 1) and the conditions in which the lc-excess can be used remain unclear [9,19].…”
Section: Introductionmentioning
confidence: 99%